ANALYSIS OF CRITICAL THINKING SKILLS IN MATHEMATICS SUBJECTS OF FOURTH GRADE STUDENTS OF SD MUHAMMADIYAH SUGIO LAMONGAN - Verra Ayu Fatmawati; Mochammad Miftachul Huda; Ari Susandi (Journal of Elementary Education, 2025)
Critical thinking skills are an ability that must be possessed by students in the learning process. The process of learning mathematics is interrelated with the learning process of critical thinking in students because it trains students to solve problems that are included in the indicators of critical thinking skills. Many students are not interested in learning mathematics so that their critical thinking skills become low due to lack of problem solving. This study aims to determine the critical thinking skills of fourth grade elementary school students in mathematics. This research uses a qualitative descriptive method. Qualitative descriptive method is a research method carried out based on a qualitative approach that covers natural conditions and problems about a person's experience in the place under study. The instruments used in collecting research data are observation, interviews, questionnaires, and documentation studies. The subjects of this research were students of SD Muhammadiyah Sugio Lamongan. The focus of this research is the ability of critical thinking in grade IV students at SD Muhammadiyah Sugio Lamongan. The results of this study indicate that students' critical thinking skills in math subjects are still fairly low. This is because among the six indicators of critical thinking skills observed there are still many students who have not fulfilled these indicators.